On Aboriginal Representation in the Gallery - Jessup, Lynda; Bagg, Shannon (Canadian Museum of Civilization, 2002)
This book provides a glimpse of thirteenth-century life and death in a southern Ontario Iroquoian community. The renovation of a Toronto soccer field in 1997 resulted in the accidental discovery of an Iroquoian ossuary–a large pit containing the remains of at least 87 people. The pit was excavated and recorded, and the remains reburied in accordance with the wishes of the Six Nations Council of Oshweken. Scientific analyses of the bones resulted in a remarkably detailed demographic profile of the Moatfield people, along with indicators of their health and diet. The book reports these findings and includes a complete database of maps and profiles on an accompanying CD-ROM. Ronald F. Williamson is president of Archaeological Services Inc., Toronto. Susan Pfeiffer is professor of anthropology at the University of Toronto. Source: Publisher
Section: XXX-310 p. : illustrations ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé